AMBIGUITY DETECTIN TECHNIQUES OF SRS: CLASSIFICATION,MERITSANDDEMERITS (International Journal of Food and Nutritional Sciences, 2022)
The success rate of a software project can be directly influenced by the Quality of Software Requirements Specification. There are different characteristics which affects the quality of SRS.As stated by IEEE Standard 830 there are eight characteristics (Unambiguity, Correctness, Completeness, Consistency, Ranked for importance and or stability, Modifiability, Verifiability and Traceability) which affect the Quality of SRS. Unambiguity is the one of the important characteristic which also influences the other characteristics like Correctness, Verification and Traceability of SRS. Out of eight characteristics stated by IEEE three characteristics are directly or indirectly affected by the ambiguity of the SRS. This indicates the importance of identification of ambiguity in the SRS documents. So far so many techniques were developed for detecting the same, but every technique has its own merits and demerits. This paper explores different approaches used for detecting the ambiguities in the SRS document and provides clear distinction among them.